Comparative study of aggression – Dangerousness on patients with paranoid schizophrenia: Focus on demographic data, PANSS, drug use and aggressiveness. (September 2018) - Ntounas, Petros; Katsouli, Alexandra; Efstathiou, Vasiliki; Pappas, Dimitris; Chatzimanolis, Pythagoras; Touloumis, Charalampos; Papageorgiou, Charalampos; Douzenis, Athanassios
Abstract: This cross sectional study aimed to compare the differences in psychopathology of Greek homicide and homicide attempters, patients with schizophrenia, with non violent individuals, suffering from schizophrenia. The study compared three Groups of 220 men, diagnosed with schizophrenia: (a) Group Α (Schizophrenia – No violence, (b) Group Β (Schizophrenia – with violence or violent crime), (c) Group C (Schizophrenia – not guilty by reason of insanity – violent crime). Several psychometric tools were used, such as M.I.N·I (Mini-International Neuropsychiatric Interview), PANSS scale (Positive and Negative Symptoms Scale). Most subjects suffered from paranoid schizophrenia. On factors such as demographic characteristics (i.e. current occupational status, living status), statistically significant findings were shown for Groups B and C vs Group A. Predisposing psychosocial factors, such as family conflicts and aggressiveness against family, were found to be statistically significant in differentiating violent versus nonviolent individuals with psychosis. They differed significantly in factors like history of juvenile delinquency, but also in the type of aggressiveness in general. These differences were confirmed on PANSS scale. In conclusion, the longer the history of aggressiveness is presented, the greater the chances are of individuals falling into Group C and it is possible to spend several years from the onset of the disease until the moment of crime.